New molecule in the etiology of schizophrenia: Urotensin II. Issue 2 (30th October 2013) - Bulbul, Feridun; Alpak, Gokay; Unal, Ahmet; Copoglu, Umit Sertan; Orkmez, Mustafa; Virit, Osman; Tarkcıoglu, Mehmet; Savas, Haluk A.
<x xml:space="preserve">Abstract</x> Aims Urotensin II (U‐II) is a cyclic peptide that was first isolated from the caudal neurosecretory system of goby fish. U‐II receptors were detected in the vascular endothelium, brain and kidney cortex. Urotensin is by far the most powerful vasoconstrictor identified. U‐II molecules were previously isolated from the brain of rats and were shown to have an impact on rat behavior. The aim of the present study was to measure the level of U‐II molecule in schizophrenia patients and to investigate whether the U‐II level is associated with the etiology of schizophrenia. Methods Forty schizophrenia patients who were followed at Gaziantep University Faculty of Medicine Department of Psychiatry Psychotic Disorders Unit and 40 healthy volunteers were enrolled in this study. Blood samples were taken from the antecubital vein after 12‐h fasting. U‐II level was measured on ELISA. Results The U‐II level in schizophrenia patients was significantly higher than in the control group. U‐II level was not different with regard to gender in either group. U‐II level was not different between subgroups of schizophrenia. No significant correlation was found between U‐II level, Positive and Negative Syndrome Scale and Clinical Global Impression–Severity scale scores. Conclusion U‐II level was higher in schizophrenia patients, indicating that U‐II level may be related to the etiology of the disease.